Design Of An Early Warning System For Fire Based On The Internet Of Things (IOT) Using Nodemcu Esp8266 - Thoriq Ahmad Qushoyyi; Syarifuddin Nasution; Ainul Haq (International Journal of Electrical Engineering, Mathematics and Computer Science, 2025)
Fire is one of the incidents that disturbs homeowners because of the fire that will drain property and can claim lives when there is a lack of anticipation and minimal ignorance of the incident, such as when a fire occurs there is no early warning to the homeowner, this is also a cause of fire. The cause of the fire can be caused by a gas leak, electrical short circuit or caused by the community itself. Based on these problems, a solution is needed to create a safety system technology to be applied to the home kitchen, namely the design of an early detection system for fires based on the Internet Of Things (IoT) using ESP8266 which is useful for monitoring kitchen conditions and will automatically send a notification of the kitchen condition if the sensor reads an incident. The Hardware Design uses several tools consisting of ESP8266, Arduino R3. Jumper Cables, Fire Sensors, MQ-2 Gas Sensors, Mini Fans, Mini Water Pumps, Relays, Buzzers. and for the software design using Arduino IDE for system programming and Blynk as an application to display notifications. The designed system will be tested using black box testing which is used to determine whether the designed system will meet the specified parameters or not, and the results of the design state that the system is in accordance with the parameters used.